ACTIVATED CARBON PREPARED FROM COCONUT SHELL POWDER WITH LOW ACTIVATION TIME AS SUPERCAPACITOR ELECTRODES - Rosi, Memoria; Fatmizal, M. Nanang Ziad; Siburian, Dedy Hendra; Ismardi, Abrar (Universitas Mataram, 2023)
In this study, we prepared activated carbon from coconut shell with a low activating time for activated carbon (AC). The coconut shell powder (< 100 Âµm) allows for an effective pyrolysis process and low activation time (30 min) that reduces the cost of production. The AC has characteristics of micropore with average size of 1.9 nm and a surface area of 460.50 m2/g. For supercapacitor electrode, the AC electrodes have capacitance of 50, 66, and 67.5 F/g when 0.5 M, 1 M, and 2 M of Na2SO4 electrolyte was being inserted, respectively. In addition, the equivalent series resistance (ESR) of the AC electrode was 6.6; 4.3, and 4.1 W for 0.5 M, 1 M and 2 M of Na2SO4 electrolyte. These results indicate that the coconut shell powder can be an alternative source for supercapacitor application with moderate performance.